Epoxy nanocomposites with reduced coefficient of thermal expansion. Issue 26 (7th March 2019) - Hirata, Tatsuya; Li, Peng; Lei, Fan; Hawkins, Spencer; Mullins, Michael J.; Sue, Hung‐Jue
ABSTRACT: Control of the coefficient of thermal expansion (CTE) of polymeric materials is critical in many applications, particularly the electronics industry where CTE mismatches have caused failures. In theory, adding exfoliated nanoplatelets with high aspect ratios would offer an effective solution for reducing CTE, but reported results have not been compelling due to poor dispersion. In this study, α‐zirconium phosphate (ZrP) nanoplatelets, along with organic surfactants, were added to epoxy thermosets. The CTE reduction and glass‐transition temperature ( T g ) were measured while the molecular weight of the surfactant was varied. High‐molecular‐weight surfactants are effective for ZrP exfoliation and dispersion, but they can also lead to a reduction in T g and hinder the drop in CTE. A combination of two low‐molecular‐weight tetrabutylammonium hydroxide and 2‐methoxyethylamine surfactants for exfoliation of ZrP were found to give a CTE reduction of 40% with just 3.5 vol % of ZrP added. This CTE reduction correlates well with theory. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47703. Abstract :